New Directions: Privatization and Higher Education in Alberta - Rae, Peter (Canadian Journal of Higher Education, 1996)
Recent Alberta initiatives in higher education reflect a growing Canadian preoccupation with privatization. Opposing ideological forces offer conflicting assessments of privatization in higher education: as endangering the very nature and goals of higher education or as simply providing additional resources and greater consumer choice. Privatization in higher education is identified as a shift in the balances of finance or control from public to private. It is implemented in higher education through the encouragement or toleration of private educational institutions or through the fostering of private investment in public systems. Alberta's 1994 restructuring of postsecondary education is identified as an approach which implements a privatization agenda while claiming to safeguard public interests.